Analysis of Factors Influencing the Performance of Halal Product Process Facilitator at IAI TAZKIA - Az Zahra Zaahiroh; Anita Priantina (Proceedings of Femfest International Conference on Economics, Management, and Business, 2024)
The purpose of this study is to see whether attitude, subjective norm, behavioral control, and initiative have significant relationship with performance of Halal Product Process Facilitator (PPH). The data analysis method used is Partial Least Square Structural Equating Modeling (PLS-SEM), online questionnaires were distributed to all of the IAI Tazkia’s Halal Product Process Facilitator (PPH). This study found that the variables of behavioral control and initiative have the positive and significant effect on the performance, where the variables of attitude and subjective norm does not indicate the significant relationship with the performance variable.